2017
DOI: 10.1017/jfm.2017.299
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of a compliant wall in a turbulent channel flow

Abstract: Interaction of a compliant wall with a turbulent channel flow is investigated experimentally by simultaneously measuring the time-resolved, three-dimensional (3D) flow field and the two-dimensional (2D) surface deformation. The optical set-up integrates tomographic particle image velocimetry to measure the flow with Mach–Zehnder interferometry to map the deformation. The Reynolds number is $Re_{\unicode[STIX]{x1D70F}}=2300$, and the Young’s modulus of the wall is 0.93 MPa, resulting in a ratio of shear speed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
65
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 116 publications
12
65
4
Order By: Relevance
“…These findings may explain why recent numerical studies consistently report either an increase in drag or a statistically unchanged flow field in the presence of travelling wave-like wall deformations (Xu et al 2003;Fukagata et al 2008;Rosti & Brandt 2017;Xia et al 2017). More recently, Zhang, Miorini & Katz (2015), Zhang et al (2017) have reported pioneering experiments that capture compliant wall deformations and turbulent velocity field in a water channel simultaneously. These experiments confirmed unequivocally the existence of travelling waves on the surface.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…These findings may explain why recent numerical studies consistently report either an increase in drag or a statistically unchanged flow field in the presence of travelling wave-like wall deformations (Xu et al 2003;Fukagata et al 2008;Rosti & Brandt 2017;Xia et al 2017). More recently, Zhang, Miorini & Katz (2015), Zhang et al (2017) have reported pioneering experiments that capture compliant wall deformations and turbulent velocity field in a water channel simultaneously. These experiments confirmed unequivocally the existence of travelling waves on the surface.…”
mentioning
confidence: 85%
“…A water channel with L * 2 = 0.2 m height is considered, with intermediate Reynolds number, Re τ = 1000. Such flow conditions can be tested in various experimental facilities (Schultz & Flack 2013;Zhang et al 2017). The #40 parameter set (equivalent to #44) is used because this compliant wall model leads to drag reduction in both low and intermediate Reynolds number channel flows.…”
Section: Appendix Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of the most important assumptions on the results is addressed in § 6. The deformation of a compliant coating in a turbulent flow is computed analytically using the one-way coupling method: turbulent flow stresses deform the compliant coating, but these coating deformations have negligible influence on the turbulent flow, as in the recent study by Zhang et al (2017). The turbulent surface stresses are expressed as a sum of streamwise-travelling and spanwise-homogeneous waves (cf.…”
Section: Summary Of Model and Assumptionsmentioning
confidence: 99%
“…The latter was identified by a pronounced increase of the streamwise velocity fluctuations and the Reynolds stress, which suggests that turbulence was generated by the soft wall. Zhang et al (2017) investigated a compliant coating in a turbulent channel flow at Re τ = 2300. They report simultaneous measurements of the time-resolved, three-dimensional flow field (using particle image velocimetry (PIV)) and the twodimensional surface deformation (using Mach-Zehnder interferometry (Zhang, Miorini & Katz 2015)).…”
mentioning
confidence: 99%